When do Lithuanian NGDOs Succeed in Influencing Foreign Policy? - Gadeikienė , Marta (Politologija, 2022)
The literature indicates an ever-growing involvement of non-governmental organisations (NGOs) in foreign policy and hence an increasing potential for them to exert influence over it. Approaching foreign aid policy as a suitable empirical indicator of a country’s foreign policy, this paper examines the case of Lithuanian development NGOs’ (NGDOs’) influence over bilateral foreign aid policy. Based on the mechanistic approach to social science, this paper demonstrates that NGDO influence is observed when an NGDO has resources to assist decision-makers in policy implementation; when it behaves strategically; and when decision-makers’ access to these resources is threatened. Although other NGDO’s resources are insufficient to result in the NGDO being able to exercise influence, they help to strengthen the long-term collaborative relationship with decision-makers, which is necessary for the micro-phenomenon of NGDO influence to occur. The paper concludes that the potential influence of Lithuanian NGDOs is limited, constrained by the scant demand for NGDOs’ resources and the unconducive institutional setting. But the paper identifies low issue salience and a focused concentration of valuable resources within Lithuanian NGDOs as factors which increase the likelihood of NGDO influence.
Keywords: Lithuanian NGDOs; policy influence; resources; foreign aid policy; inside lobbying